Extensive Inflammatory Pseudotumour of cranial base – a rare case which has responded well to cyclophosphamide and steroid therapy - Abdullah, Kahairi; Raja Lope Ahmad, Raja Ahmad Al'konee; Leman, Wan Ishlah; K.S, Sathananthar (2010)
Introduction: Inflammatory Pseudotumour (IP) of the head and neck is a rare disease. Due its rarity, diagnosis is often delayed which cause significant morbidity to the patient. Objective: To illustrate a case of extensive inflammatory pseudotumour involving the floor of cranial base which demonstrate an aggressive behavior clinically and radiologically. Treatment and Result: The clinical presentations were improved with oral cyclophosphamide in combination with oral steroid which were given for a period of three month. Conclusion: This case has illustrated a rare extensive IP of cranial base which responded well toward combination of cyclophosphamide and high dose steroid.